Preliminary Study on The Effect of Inlet Pressure of Standard Slit Interdigital Micro Mixer Towards Mixing by Computational Fluid Dynamics - Termizi, Siti Nor Azreen Ahmad; Shukor, Syamsul Rizal Abd. (2013)
The aim of this work is to visualize the velocity profile and concentration profile of the mixing element of standard slit interdigital micro mixer (SSIMM) by simulating it in computational fluid dynamic (CFD).